2005
DOI: 10.1210/me.2004-0468
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Actions of Membrane-Targeted Versus Nuclear Localized Estrogen Receptors in Breast Cancer Cells

Abstract: Estrogens regulate multiple activities in breast cancer cells, including proliferation. Whereas these hormones are most commonly known to regulate gene transcription through direct interaction with estrogen receptors (ERs) and with specific DNA sequences of target genes, recent studies show that ER also activates a number of rapid signaling events that are initiated at the cell membrane. To study the membrane-initiated effects of estrogen and separate them from the activities initiated by the nuclear localized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 65 publications
(73 reference statements)
2
47
1
Order By: Relevance
“…The p/m-AR described in the current study is structurally different from the membrane-targeted ER described by Rai et al (48). Membrane-targeted-ER was engineered by N-terminal myristoylation and C-terminal palmitoylation, while lacking a nuclear localization sequence (48).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The p/m-AR described in the current study is structurally different from the membrane-targeted ER described by Rai et al (48). Membrane-targeted-ER was engineered by N-terminal myristoylation and C-terminal palmitoylation, while lacking a nuclear localization sequence (48).…”
Section: Discussionmentioning
confidence: 85%
“…Membrane-targeted-ER was engineered by N-terminal myristoylation and C-terminal palmitoylation, while lacking a nuclear localization sequence (48). In contrast, we engineered p/m-AR to express a short peptide with a myristoylation and palmitoylation site linked to the N-terminal domain of AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last few years, we and others have identified several synthetic compounds that, unlike estradiol, can selectively activate kinase-initiated routes by which the estrogen receptor (ER) controls gene transcription (28,38,60). By use of these compounds, substantial evidence that kinase-mediated effects on gene transcription are dissociable from direct cis or trans effects on transcription has been obtained (28,38,39,54). Moreover, the use of selective activators of kinases, as well as compounds that dissociate the classical genomic actions of the estrogen receptor from cross talk with other transcription factors (8,56), has provided extensive proof of the general concept that it is possible to eliminate the uterotropic activity of estrogens while retaining other nonreproductive actions.…”
mentioning
confidence: 99%
“…[18][19][20] This can be partially explained by differences in the expression levels of ER, EGFR, and the HER-2 receptor. [21][22][23][24] Furthermore, it has been suggested that multiple mechanisms exist by which estrogen stimulation can lead to ERK activation. 15,25 This underscores the need for a study using an appropriate cell type and consistent experimental conditions to elucidate the mechanisms by which E2 and tamoxifen induce ERK phosphorylation.…”
Section: Introductionmentioning
confidence: 99%